Genetic characterization of Biochemical contents of pigeon pea (cajanus cajan millsp) (2009)
Purpose – The purpose of this paper is to characterize 25 collections of pigeon pea from south-west Nigeria using nutritional and anti-nutritional contents of the seeds. Design/methodology/approach – The nutritional and anti-nutritional constituents of 25 collections of pigeon pea were determined. Data collected were subjected to correlation, principal components and fastclus analyses. Findings – Ariation among the collections for the nutrient contents was low. Trypsin inhibitor content had the highest variability ranging between 21.74 and 35.43 Tiu/mg. Protein and trypsin inhibitor contents were significant and negatively correlated. The first three principal components explained 74.0 per cent of the total variation. Fastclus procedures grouped the collections into three. Members of cluster 1 had the highest value for protein and the lowest concentrations of the antinutritional factors (ANFs). Cluster 2 possessed relatively low protein with high level of ANFs while cluster 3 was intermediate between clusters 1 and 2 for most characters. Originality/value – The results indicate that members of cluster 1 with high protein and low levels of ANFs are good candidates in breeding/selecting pigeon pea cultivars with enhanced nutritional values